Loss of Mitochondrial Pyruvate Carrier 2 in Liver Leads to Defects in Gluconeogenesis and Compensation via Pyruvate-Alanine Cycling - McCommis, Kyle S. (Cell Metab, 2015)
Pyruvate transport across the inner mitochondrial membrane is believed to be a prerequisite step for gluconeogenesis in hepatocytes, which is important for maintenance of normoglycemia during prolonged food deprivation, but also contributes to hyperglycemia in diabetes. To determine the requirement for mitochondrial pyruvate import in gluconeogenesis, mice with liver-specific deletion of mitochondrial pyruvate carrier 2 (LS-Mpc2(−/−)) were generated. Loss of MPC2 impaired, but did not completely abolish, hepatocyte pyruvate metabolism, labelled pyruvate conversion to TCA cycle intermediates and glucose, and glucose production from pyruvate. Unbiased metabolomic analyses of livers from fasted LS-Mpc2(−/−) mice suggested that alterations in amino acid metabolism, including pyruvate-alanine cycling, might compensate for loss of MPC2. Indeed, inhibition of pyruvate-alanine transamination further reduced mitochondrial pyruvate metabolism and glucose production by LS-Mpc2(−/−) hepatocytes. These data demonstrate an important role for MPC2 in controlling hepatic gluconeogenesis and illuminate a compensatory mechanism for circumventing a block in mitochondrial pyruvate import.